EVALUATION OF TREATMENT OUTCOMES OFANKLE FRACTURES USING LOCKING PLATE THROUGH MINIMALLY INVASIVE APPROACH WITH PREOPERATIVE 3D PRINTING ASSISTANCE - Thanh Toan, Vo; Thien Duc, Nguyen; Phi Trinh, Nguyen (Journal of Health and Aging, 2025)
To assess the clinical effectiveness of 3D-printed models in minimally invasive plate osteosynthesis (MIPO) for ankle fractures, compared with conventional surgical planning. Methods: A quasi-experimental study was conducted at Thong Nhat Hospital from January 2024 to January 2025. Twenty-eight patients with ankle fractures were enrolled and divided equally into two groups (n = 14 each): one managed with 3D-assisted preoperative planning and the other with conventional methods. Results: The 3D-assisted group demonstrated significantly better intraoperative and postoperative outcomes. Mean operative time was shorter (55.3 ± 6.6 vs. 68.1 ± 5.3 minutes, p = 0.001), blood loss was lower (75.5 ± 10.2 vs. 110.3 ± 15.7 ml, p < 0.001), and C-arm exposure was reduced (10.8 ± 1.1 vs. 17.2 ± 1.5 shots, p = 0.003). Functional recovery was superior, with higher Rasmussen scores at 3 months (26.7 ± 1.3 vs. 23.4 ± 2.1, p = 0.002). Postoperative complications were also less frequent in the 3D group. Conclusion: Preoperative 3D printing significantly enhanced surgical accuracy and clinical outcomes in ankle fracture management. Patients treated with 3D assistance experienced shorter operations, reduced intraoperative blood loss, fewer fluoroscopic exposures, improved functional recovery, and a lower complication rate.
Keywords: 3D printing; locking plate; ankle fracture; minimally invasive osteosynthesis